Trend Analysis of Long-Term Rainfall Data for Monsoon Season of Kharun Catchment - Vipin Kumar Mishra; Dhiraj Khalkho; Shruti Verma (International Journal of Rural and Regional Development, 2025)
This research paper investigates the trends in monsoon season rainfall over a 31-year period (1990–2021) using the non-parametric Mann–Kendall test. A range of statistical methods were utilized to analyze the rainfall data, providing valuable insights into its temporal patterns and trends. The correlation coefficient, measured by Kendall's Tau, exhibited a minimal positive correlation of 0.004 between years and their corresponding rainfall, quantities. This implies a slight tendency for increased rainfall with the passage of time. The Mann–Kendall statistic (S) yielded a value of 2 from a two-tailed test, accompanied by a p-value of 0.98 revealing that there is no statistically significant trend in the rainfall data. This implies that the observed fluctuations in monsoon rainfall over the 31-year span are more likely attributable to natural variability rather than a consistent upward or downward trajectory. Moreover, employing an alpha level of 0.050, the Sens's slope (Q) of 0.119 demonstrated a marginal positive slope, indicating a minor rise in rainfall over time. However, this trend lacks the strength required for statistical significance. The Z value of 1.98 further reinforces the insignificance of the observed trend, aligning with the null hypothesis of no trend.
Keywords: Mann–Kendall test; Sen’s slope estimator; Trend analysis; rainfall